Twenty one new species of Megaselia Rondani (Diptera: Phoridae) from Iran - Khameneh, Roya Namaki; Khaghaninia, Samad; Disney, R. Henry L.; Maleki-Ravasan, Naseh (Zootaxa, 2019)
The following 21 new species from Iran are described, 7 from East Azerbaijan province Megaselia ajabshirensis, M. chicheckliensis, M. exkaleybar, M. kaleybarensis, M. qurigolensis, M. shabestarensis, M. zonuzensis. and 14 from West Azerbaijan province, M. evogliensis, M. farshbafi, M. ghalateshahensis, M. haddadi, M. hejazii, M. khaghaniniai Namaki & Disney, M. khoyensis, M. ledzona, M. mahabadensis, M. miandoabensis, M. namakiae Khaghaninia & Disney, M. pereensis, M. yaseri, M. zarghanii.